One Parameter Family of Jordanian Twists - Meljanac, D.; Meljanac, S.; Škoda, Z.; Štrajn, R. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
We propose an explicit generalization of the Jordanian twist proposed in r-symmetrized form by Giaquinto and Zhang. It is proven that this generalization satisfies the 2-cocycle condition. We present explicit formulas for the corresponding star product and twisted coproduct. Finally, we show that our generalization coincides with the twist obtained from the simple Jordanian twist by twisting by a 1-cochain.